CORRELATIONS BETWEEN MICROVASCULAR AND NEURODEGENERATIVE OCULAR CHANGES IN DIABETIC PATIENTS - Carmen Tiutiuca; Geanina Totolici; Dinu Bogdan Tiutiuca; Lucian Indrei; Ana Magdalena Bratu (Romanian Society of Oral Rehabilitation, 2023)
Glaucoma is a progressive, degenerative optic neuropathy that significantly affects visual function and quality of life. Glaucoma is a major public health problem worldwide because of the high risk of blindness. Early diagnosis increases the likelihood that patients will maintain useful visual function throughout life. To this end, it is important to identify all risk factors, such as diabetes mellitus which, due to its increased incidence in the general population, appears to play a key role in the determinism of the disease. The aim of this paper is to review the pathophysiological similarities between the two diseases as well as data from the literature on how diabetes affects the pathogenesis of primary open-angle glaucoma. It also provides recommendations for screening diabetic patients that can be implemented at reasonable cost, which can lead to early diagnosis of glaucomatous disease and improved quality of life.